Influence of new broadleaf herbicides on weed control, seed yield and quality of some wheat ( Tritcum aestivum) cultivars - Chopra, Neelam Kumar; Chopra, Nisha; Sinha, S N (The Indian Journal of Agricultural Sciences, 2008)
A field experiment was conducted at Karnal. Haryana during winter (rabi) seasons of 2000-01 and 2001-02 to evaluate the effect of new broadleaf herbicides, viz. carfentrazone ethyl and metsulfuron methyl for weed control, yield and quality of different wheat (Triticum aestivum L.emend. Fiori & Paol.) cultivars raised for seed production. Cultivars ’HD 2687’, ’HD 2643’ and ’HD 2733’ smother the weeds more efficiently than the ’HDR 77’, ’HD 2380’and ’HD 2329’,’HD 2687’ recorded maximum grain yield (4.22 tonnes/ha) across weed control levels which was significantly higher than the ’HDR 77’, ’HD 2380’ and ’HD 2329’. Both carfentrazone and metsulfuron did not affect the spike morphology of different wheat cultivars compared to 2,4-D. Carfentrazone 20g/ha and metsulfuron 4 g/ha reduced the weed density and weed dry weight significantly over the weed check, carfentrazone l0g/ha and 2,4-D 500 g/ha. Carfentrazone 20 g/ha and metsulfuron 4 g/ha controlled 83.7 and 84.1% of broadleaf weeds-respectively and increased the seed yield significantly over the other treatments. Carfentrazone at 10 and 20g/ha and metsufuron 4g/ha did not cause any adverse effect on seed germination and seed vigour hence can be safely used in seed production plots of wheat.